O processo de comercialização do turismo de base comunitária no Brasil:: desafios, potencialidades e perspectivas (Sustainability in Debate, 2012)
The community-based tourism (CBT) has been consolidated over the last decade in Brazil as a wayof tourism organization at the local scale. However, much remains to be done to realize its fullpotential to support the social development of local communities. In this paper we discuss the issueof market access, suggested by some studies as critical to the economic sustainability of communityenterprises. We start from the analysis of some, national and international, documents and researchto propose strategic guidelines for the process of marketing of CBT initiatives and routes.